Assessing the Invasion Risk of Eucalyptus in the United States Using the Australian Weed Risk Assessment. (4th December 2012) - Gordon, Doria R.; Flory, S. Luke; Cooper, Aimee L.; Morris, Sarah K.
Abstract : Many agricultural species have undergone selection for traits that are consistent with those that increase the probability that a species will become invasive. However, the risk of invasion may be accurately predicted for the majority of plant species tested using the Australian Weed Risk Assessment (WRA). This system has been tested in multiple climates and geographies and, on average, correctly identifies 90% of the major plant invaders as having high invasion risk, and 70% of the noninvaders as having low risk. We used this tool to evaluate the invasion risk of 38 Eucalyptus taxa currently being tested and cultivated in the USA for pulp, biofuel, and other purposes. We predict 15 taxa to have low risk of invasion, 14 taxa to have high risk, and 9 taxa to require further information. In addition to a history of naturalization and invasiveness elsewhere, the traits that significantly contribute to a high invasion risk conclusion include having prolific seed production and a short generation time. Selection against these traits should reduce the probability that eucalypts cultivated in the USA will become invasive threats to natural areas and agricultural systems.